Mesenchymal stem cells internalize Mycobacterium tuberculosis through scavenger receptors and restrict bacterial growth through autophagy. Issue 1 (December 2017) - Khan, Arshad; Mann, Lovepreet; Papanna, Ramesha; Lyu, Mi-Ae; Singh, Christopher; Olson, Scott; Eissa, N.; Cirillo, Jeffrey; Das, Gobardhan; Hunter, Robert; Jagannath, Chinnaswamy
Abstract Human mesenchymal stem cells (MSCs) express scavenger receptors that internalize lipids, including oxidized low-density lipoprotein (oxLDL). We report that MSCs phagocytoseMycobacterium tuberculosis (Mtb) through two types of scavenger receptors (SRs; MARCO and SR-B1), as blockade of the receptors with antibodies or siRNA knockdown decreased the uptake of Mtb. MSCs also expressed mannose receptor (MR) that was found to endocytose rhodamine-labeled mannosylated BSA (rMBSA), though the receptor was not involved in the uptake of Mtb. Dil-oxLDL and rMBSA taken up into MSC endosomes colocalized with Mtb phagosomes, thus suggesting that the latter were fusion competent. Phagocytosed Mtb did not replicate within MSCs, thus suggesting an intrinsic control of bacterial growth. Indeed, MSCs exhibited intrinsic autophagy, which was up-regulated after activation with rapamycin. SiRNA knockdown of autophagy initiator beclin-1 enhanced Mtb survival, whereas rapamycin-induced autophagy increased intracellular killing of Mtb. In addition, MSCs secreted nitric oxide after Mtb infection, and inhibition of NO by N(G)-monomethyl-L-arginine enhanced intracellular survival of Mtb. MSCs can be grown in large numbersin vitro, and autologous MSCs transfused into tuberculosis patients have been found to be safe and improve lung immunity. Thus, MSCs are novel phagocytic cells with a potential for immunotherapy in treating multidrug-resistant tuberculosis.